Retardo Mental Sociocultural o Diferencias Cognitivas en niños de nivel socioeconómico bajo - Bravo Valdivieso, Luis (1993)
The aim of this paper is to analize the term "sociocultural mental relardation" (M.R.) appliable in the U.S.A. to minorities group children who have got bordeline or low I.Q. and school leaming difficulties. In the Latin America context this tenn could be applied to the majority group of children as well, because of the high rate of school failure and the percenlage of "bordeline" o low I.Q. children, within the lower socio economic and culturallevels of the population The author discusses severa! Latinamerican studies and compares the WISC-R scores of Chilean and American children. It is concluded that the tenn «sociocultural mental relardation» is an inadecuate concept to explain the cognitive and verbal differences between subjects of middle and low socioeconomic level.